“Humanitas” and vocational education as an opportunity to tackle the “leadership of incompetence” in the “second age” of machines - Alessandrini, Giuditta (Formazione & insegnamento, 2019)
This paper focalize some conceptual pathways to broaden a critical discussion about acceptable ways to “salvage”, within social contexts, a central focus on human values, as well as to hinder the legitimacy of incompetence and of a “regressive” modernisation. These argumentations are interwoven with a brief resume of the Author’s 40 years long study activity.